Applied and industrial mathematics in Italy : (World Scientific, 2005)
Industrial mathematics is evolving into an important branch of mathematics. Mathematicians, in Italy in particular, are becoming increasingly aware of this new trend and are engaged in bridging the gap between highly specialized mathematical research and the emerging demand for innovation from industry. In this respect, the contributions in this volume provide both R&D workers in industry with a general view of existing skills, and academics with state-of-the-art applications of mathematics to real-world problems, which may also be incorporated in advanced courses.